Governance Strategies of BUMDes in Improving Household Economic Standards in Mangega Village - Junaedi, Erina (SAINTIS Publishing, 2024)
The village of Man’gega is one of the villages that has a Village-Owned Enterprise (BUMDes) with substantial management funds, amounting to 20 million rupiahs. This budget serves as a starting point for progress and innovation in undertaking business ventures. However, the current situation is different. Despite having a large capital, the BUMDes engages in business activities that lack creativity and fail to create its own products with entrepreneurial value. Ideally, BUMDes Maksaira should adopt more effective strategies and tactics.The purpose of this study is to determine the impact of implementing BUMDes strategies in running businesses on improving household economic income. The usefulness of this research lies in providing information and evaluation materials for the community and BUMDes Maksaira in Man’gega village.This study employs a qualitative research approach. The type of research is a survey, while the method used is descriptive analysis. Data were collected through observation, interviews, and documentation.The business activities carried out by BUMDes Maksaira have become a thing of the past. The provision of nine basic needs (sembako) to the village community did not run effectively. Many were unable to repay the costs of obtaining the sembako, which became a burden for BUMDes. The stagnation of the business was also caused by mismanagement, such as BUMDes members themselves being among those obtaining sembako.The recommendations of this study are addressed to the village authorities of Man’gega and BUMDes Maksaira to promptly monitor prices or coordinate with government agencies, in this case, the Industry and Trade Cooperative Office (DISPRINDA KOP), to regulate the prices of sembako sold by BUMDes Maksaira. Alternatively, the business direction could be shifted from selling sembako to focusing on mangrove tourism.